1989
DOI: 10.5636/jgg.41.461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of equatorial electrojet intensity on its landmark distances.

Abstract: From the correlations of seven landmark distances, s, of the equatorial electrojet with its peak eastward current intensity Jo and its space gradient dJo/ ds, we find that the entire electrojet current system, with its magnetic field, tends to contract; consequently, the current and magnetic field foci, as well as contours of equal current intensity or of equal magnetic field, move towards the magnetic dip equator as the electrojet intensity increases. Furthermore, for a given increase in intensity, the greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The increase of the peak current density needed to decrease the half thickness, p km, by unit amount is greater for a small half thickness than for a large half thickness; about 2 A km-2 per km for a half thickness of about 5.4 km, but about 1 A kmP2 per km for a half thickness of about 6.04 km. In this case, actual in situ measurements have fully confirmed results from model fittings by Onwumechili & Ogbuehi (1967), Onwumechili & Agu (1981a) and Onwumechili et al (1989). However, this is the first time the resulting contraction of the electrojet has been demonstrated with a vertical dimension of the electrojet.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The increase of the peak current density needed to decrease the half thickness, p km, by unit amount is greater for a small half thickness than for a large half thickness; about 2 A km-2 per km for a half thickness of about 5.4 km, but about 1 A kmP2 per km for a half thickness of about 6.04 km. In this case, actual in situ measurements have fully confirmed results from model fittings by Onwumechili & Ogbuehi (1967), Onwumechili & Agu (1981a) and Onwumechili et al (1989). However, this is the first time the resulting contraction of the electrojet has been demonstrated with a vertical dimension of the electrojet.…”
Section: Discussionsupporting
confidence: 72%
“…More recently, Onwumechili, Agu & Ozoemena (1989) showed that not only the width, but the entire electrojet current and its magnetic field contours contracted as the current intensity increased. It is important to investigate whether the thickness also contracts in the same way as the width when the intensity increases.…”
Section: The Relationship Between Current Intensity and Thickness Of mentioning
confidence: 99%
See 1 more Smart Citation